STRATEGI PENGEMBANGAN AGRIBISNIS PETANI CABAI RAWIT DI KECAMATAN KOLONO TIMUR KABUPATEN KONAWE SELATAN - Rahman, Muhammad Alfian; Sidu, Dasmin; Rela, Iskandar Zainuddin (Fakultas Pertanian Universitas Halu Oleo, 2023)
This study aims to find out the agribusiness condition and agribusiness development strategy carried out by cayenne pepper farmers in East Kolono District, South Konawe Regency. This research was conducted in East Kolono District, South Konawe District. Location determination is carried out purposively with several considerations, including that East Kolono District is one of the cayenne pepper commodity producing areas in South Konawe Regency, East Kolono sub-district has farmers who have developed cayenne pepper and made it the main commodity to cultivate, and the location of the research is easy to reach, as well as time considerations, and the existence of facilities in the form of sub-district offices making it easier for researchers to collect data. This study uses qualitative methods, using the analysis proposed by Miles and Huberman, namely data reduction, data presentation and preliminary conclusions. The results of this research on the agribusiness of cayenne pepper farmers in East Kolono District were carried out in a conventional way and have not involved supporting institutions optimally. while the agribusiness development strategy of cayenne pepper farmers in East Kolono District applies a devensive strategy or running a business based on rationality.